MICRO RNAS IN HIGH-GRADE GLIOMAS: WHAT IS THEIR ROLE? - Stepanović, Aleksandar (Medicinski podmladak, 2023)
High-grade gliomas are malignant tumours of the central nervous system with poor overall survival. Equivalently, glioblastoma is one of the most devastating brain tumours. Treatment for most high-grade gliomas includes surgical resection, radiotherapy, and chemotherapy. Even with all treatment modalities, at a certain point, disease progression occurs. Moreover, each of the treatment modalities can lead to different toxicities. In the last ten years, many studies have aimed to find a stable and unique biomarker that can help diagnose brain tumours, overcome treatment resistance, and improve overall survival. MicroRNAs are non-coding elements of the genome that are relatively stable in serum and plasma and can be isolated from the tissue as well.  It has been discovered that the alteration of many microRNAs can be seen in high-grade gliomas. The determined microRNA could potentially play a part in the diagnosis and prognosis of high-grade gliomas, have a therapeutic role in the treatment of high-grade gliomas or act as a predictive biomarker of treatment-induced toxicity. To achieve this, every high-grade glioma should have its own microRNA signature. Numerous studies have detected a big potential of certain microRNAs. The disadvantages of these studies are that they mostly included a small number of samples. Moreover, research into microRNA as potential therapeutic agents has primarily been based on cell lines, or xenografts. On the other hand, many microRNAs show significant alterations in high-grade gliomas, but still, their altered expression can be detected in other cancers and some non-oncological diseases. In this article, we made a critical mini-review of the role of microRNAs in high-grade gliomas.
Keywords: high-grade glioma, glioblastoma, microRNA